(untitled) (International Journal of Engineering and Computer Science, 2023)
In fact, the mushrooming development of IoT has reshaped industries and everyday life in connecting devices, networks, and systems. Accompanying this phenomenal growth are formidable challenges related to cybersecurity. The major reasons why IoT networks are more susceptible to a variety of cyber threats are the limited computational resources of devices, a lack of standardized security protocols, and the large-scale interconnectedness of devices. This paper throws light on some of the major cybersecurity threats to IoT networks, such as device vulnerabilities, network-based attacks, and data breaches. It further pays attention to the root causes of such vulnerability exposures. Further, it discusses an in-depth analysis of some of the existing defense mechanisms involving advanced authentication methods, encryption techniques, and network security measures. The work also probes into some state-of-the-art security technologies like blockchain and artificial intelligence that hold immense promise for securing IoT. It analyzes real case studies of IoT attacks, such as the Mirai Botnet and Jeep Cherokee Hack, to depict the impact of such threats and extract some helpful lessons in securing future IoT systems. The paper then concludes with discussions on the ever-evolving IoT cybersecurity landscape and how new approaches to defense strategies continue to be thought out, developed, and implemented as these risks continue to mount.